Persistent molecular microchimerism induces long-term tolerance towards a clinically relevant respiratory allergen - Baranyi, U. (2012)
BACKGROUND: Development of antigen-specific preventive strategies is a challenging goal in IgE-mediated allergy. We have recently shown in proof-of-concept experiments that allergy can be successfully prevented by induction of durable tolerance via molecular chimerism. Transplantation of syngeneic hematopoietic stem cells genetically modified to express the clinically relevant grass pollen allergen Phl p 5 into myeloablated recipients led to high levels of chimerism (i.e. macrochimerism) and completely abrogated Phl p 5-specific immunity despite repeated immunizations with Phl p 5. OBJECTIVE: It was unclear, however, whether microchimerism (drastically lower levels of chimerism) would be sufficient as well which would allow development of minimally toxic tolerance protocols. METHODS: Bone marrow cells were transduced with recombinant viruses integrating Phl p 5 to be expressed in a membrane-anchored fashion. The syngeneic modified cells were transplanted into non-myeloablated recipients that were subsequently immunized repeatedly with Phl p 5 and Bet v 1 (control). Molecular chimerism was monitored using flow cytometry and PCR. T cell, B-cell and effector-cell tolerance were assessed by allergen-specific proliferation assays, isotype levels in sera and RBL assays. RESULTS: Here we demonstrate that transplantation of Phl p 5-expressing bone marrow cells into recipients having received non-myeloablative irradiation resulted in chimerism persisting for the length of follow-up. Chimerism levels, however, declined from transient macrochimerism levels to persistent levels of microchimerism (followed for 11 months). Notably, these chimerism levels were sufficient to induce B-cell tolerance as no Phl p 5-specific IgE and other high affinity isotypes were detectable in sera of chimeric mice. Furthermore, T-cell and effector-cell tolerance were achieved. CONCLUSIONS AND CLINICAL RELEVANCE: Low levels of persistent molecular chimerism are sufficient to induce long-term tolerance in IgE-mediated allergy. These results suggest that it will be possible to develop minimally toxic conditioning regimens sufficient for low level engraftment of genetically modified bone marrow.